Data from: Community- weighted mean plant traits predict small scale distribution of insect root herbivore abundance - Sonnemann, Ilja; Pfestorf, Hans; Jeltsch, Florian; Wurst, Susanne (Dryad, 2016)
Small scale distribution of insect root herbivores may promote plant
species diversity by creating patches of different herbivore pressure.
However, determinants of small scale distribution of insect root
herbivores, and impact of land use intensity on their small scale
distribution are largely unknown. We sampled insect root herbivores and
measured vegetation parameters and soil water content along transects in
grasslands of different management intensity in three regions in Germany.
We calculated community-weighted mean plant traits to test whether the
functional plant community composition determines the small scale
distribution of insect root herbivores. To analyze spatial patterns in
plant species and trait composition and insect root herbivore abundance we
computed Mantel correlograms. Insect root herbivores mainly comprised
click beetle (Coleoptera, Elateridae) larvae (43%) in the investigated
grasslands. Total insect root herbivore numbers were positively related to
community-weighted mean traits indicating high plant growth rates and
biomass (specific leaf area, reproductive- and vegetative plant height),
and negatively related to plant traits indicating poor tissue quality
(leaf C/N ratio). Generalist Elaterid larvae, when analyzed independently,
were also positively related to high plant growth rates and furthermore to
root dry mass, but were not related to tissue quality. Insect root
herbivore numbers were not related to plant cover, plant species richness
and soil water content. Plant species composition and to a lesser extent
plant trait composition displayed spatial autocorrelation, which was not
influenced by land use intensity. Insect root herbivore abundance was not
spatially autocorrelated. We conclude that in semi-natural grasslands with
a high share of generalist insect root herbivores, insect root herbivores
affiliate with large, fast growing plants, presumably because of
availability of high quantities of food. Affiliation of insect root
herbivores with large, fast growing plants may counteract dominance of
those species, thus promoting plant diversity.
PLOSONEdataPLOSONEDATA.zip
Keywords: insect root herbivores; insect larvae; Elateridae; management intensity; Spatial distribution; plant traits